The role of faculty development in mediating the relationship between consultative management style and student learning outcomes in Cambodia’s public higher education - Holl, Piseth; Ali, Dhakir Abbas (Edelweiss Applied Science and Technology, 2025)
This study examines the influence of consultative management style (CMS) on student learning outcomes (SLOs) in Cambodian public higher education institutions, with faculty development initiatives (FDIs) assessed as a mediating factor. A survey-based quantitative method was utilized, gathering data from 305 lecturers at selected public universities. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to test four hypotheses, with validated constructs ensuring reliability and validity. The measurement model demonstrated strong reliability (CR > 0.90) and discriminant validity (AVE > 0.70). The structural model revealed that CMS significantly influences SLOs (β = 0.154, t = 2.619, p = 0.009) and FDIs (β = 0.198, t = 3.713, p = 0.000). FDIs, in turn, strongly enhance SLOs (β = 0.450, t = 8.445, p = 0.000) and significantly mediate the CMS–SLOs relationship (β = 0.089, t = 3.367, p = 0.001). The model explained 3.7% of the variance in FDIs and 25% in SLOs, with acceptable predictive relevance. CMS positively affects SLOs both directly and indirectly through FDIs. The findings underscore the importance of participatory leadership and structured faculty development programs in strengthening teaching quality and student achievement in resource-constrained higher education contexts.